2018
DOI: 10.4039/tce.2018.14
|View full text |Cite
|
Sign up to set email alerts
|

Adult size and sex ratio variation ofCerambyx welensii(Coleoptera: Cerambycidae) in Mediterranean oak (Fagaceae) woodlands

Abstract: Adult size is the trait most closely correlated with reproductive output in insects, but may also have important selective implications determining additional fitness gains. In longhorn beetles, adult size-mediated ultimate benefits may arise from mate choice, male antennal spread width or male fighting for mates. In this paper, we examined factors potentially shaping adult size of Cerambyx welensii Küster (Coleoptera: Cerambycidae), an emergent oak (Quercus Linnaeus; Fagaceae) pest. Sex ratio and adult length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…In our bioassays, C. welensii males exhibited a mating behaviour similar to that described for other Cerambycidae species, including antennal contact, dashing towards the female, licking of pronotum and basal area of elytra, and copulation attempt (Ibeas et al, 2008; Kiriyama et al, 2018). The antennal contact is favoured in C. welensii by the male antennal length which doubles the body length (Torres‐Vila et al, 2018), as found in other longhorn beetles (Hanks et al, 1996). In this context, the maxillary and/or labial palps of males could also play a role in the mating process in C. welensii , since when their antennae were coated with parafilm the dashing behaviour was impaired, but up to 80% of the copulation attempts were recovered when males were allowed to contact females with their palps (Sánchez‐Osorio et al, 2012).…”
Section: Discussionmentioning
confidence: 82%
“…In our bioassays, C. welensii males exhibited a mating behaviour similar to that described for other Cerambycidae species, including antennal contact, dashing towards the female, licking of pronotum and basal area of elytra, and copulation attempt (Ibeas et al, 2008; Kiriyama et al, 2018). The antennal contact is favoured in C. welensii by the male antennal length which doubles the body length (Torres‐Vila et al, 2018), as found in other longhorn beetles (Hanks et al, 1996). In this context, the maxillary and/or labial palps of males could also play a role in the mating process in C. welensii , since when their antennae were coated with parafilm the dashing behaviour was impaired, but up to 80% of the copulation attempts were recovered when males were allowed to contact females with their palps (Sánchez‐Osorio et al, 2012).…”
Section: Discussionmentioning
confidence: 82%
“…In our target species, data showed that Cw females are quite resilient to face significant mating delays, as there was no impact on mating success and a limited effect on reproductive output until at least 20 days of age. It is worth noting that the female lifetime mating number was lower with increased mating delays (as females had fewer opportunities to mate), but this fact likely did not have a confounding effect with delayed mating as multiple mating does not affect Cw female fecundity (Torres‐Vila et al, 2016; but see Torres‐Vila, 2024). Female longevity and egg fertility were roughly similar regardless of mating delay, similar to that reported in the scarabeid beetle Anomala orientalis Waterhouse (Wenninger & Averill, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This species has been considered a good indicator of tree hollows beetle diversity [ 53 ] Near threatened [ 23 ] Ischnodes sanguinicollis (Panzer, 1793) (Elateridae) Palearctic species [ 50 ] This species is an obligate inhabitant of tree hollows . Larvae and adults are predators [ 39 , 54 ] Vulnerable [ 23 ] Cerambyx welensii (Kuster, 1846) (Cerambycidae) Palearctic species [ 55 ] They are considered ecosystem engineers a [ 45 , 56 ].The larvae are strictly xylophagous, while adults feed mainly on tree exudates or do not feed [ 57 ] Near threatened [ 23 , 49 ] Stictoleptura trisignata (Fairmaire, 1852) (Cerambycidae) Endemic species of the Iberian Peninsula [ 58 ] The larvae of this species are considered xylophagous in different species of Quercus [ 58 ], while adults are flower visitors [ 59 ] Near threatened [ 60 ] a Are species that provide resources for other species because their activity alters the microhabitat conditions favouring other species fitness[ 45 ] …”
Section: Methodsmentioning
confidence: 99%